Fuzzy‐based adaptive control design for stochastic nonlinear time‐delay systems via event‐triggered mechanism. (27th June 2022) - Liu, Yongchao; Zeng, Bowen; Zhu, Qidan; Liu, Di
Summary: This article elaborates an adaptive fuzzy event‐triggered control design for stochastic nonlinear time‐delay systems with full‐state constraints. The prescribed constraints are ensured by employing barrier Lyapunov function. The fuzzy logic systems are exploited to approximate lumped unknown nonlinear functions. By cleverly choosing Lyapunov–Krasovskii functional, the adverse effect of time‐delay is effectively overcome. Meanwhile, the event‐triggered mechanism is adopted to save communication resource. It is illustrated that all signals of the controlled system are bounded and all states are maintained the prescribed regions at every step of recursive backstepping design. Finally, simulation results elucidate the validity of the devised scheme.